ISOLATION OF ANTIBIOTIC PRODUCING MICROORGANISMS FROM CASSAVA ROOT TAPAI BY TRADITIONAL FERMENTED - Muhiddin, Nurhayani H.; Hidayah, Nurul; Herawati, Netty; Ramlawati; Sukmadewi. M, Fitrah; Darmayani , Dwi; Marnia; Idris, Nur Afni Yunita (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Antibiotic resistance among pathogenic microorganisms has become a growing global health concern, necessitating the search for new natural sources of antimicrobial compounds. Cassava tapai, a traditional Indonesian fermented food, contains molds, yeasts, and bacteria with potential antibiotic-producing abilities. This study aimed to isolate and characterize antibiotic-producing microorganisms from cassava tapai fermented with local Sulawesi ‘Ragi’. Isolation, colony morphology characterization, and antibiotic activity tests were conducted using the Kirby–Bauer method against Escherichia coli ATCC 35218 and Staphylococcus aureus ATCC 25923. Inhibition zones were measured with a digital caliper, and data were analyzed using one-way ANOVA followed by Tukey’s HSD test or Kruskal–Wallis followed by the Mann–Whitney U test (p < 0.05). Three isolates Bb1, Bb2, and Wk3 exhibited significant antibiotic activity, with Bb1 showing stronger inhibition against E. Coli ATCC 35218. These results highlight confirms the potential of cassava tapai as a promising source of antibiotic-producing microorganisms for future antimicrobial discovery.